Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.18632/oncotarget.28000
|View full text |Cite
|
Sign up to set email alerts
|

Eltrombopag and its iron chelating properties in pediatric acute myeloid leukemia

Abstract: Pediatric acute myeloid leukemia (AML) represents 20% of total childhood leukemia diagnoses and is characterized by poor prognosis with a long-term survival rate around the 50%, when patients are properly treated. The standard treatment for pediatric AML currently consists in a combination of cytarabine (Ara-C) and antracycline. Iron plays an important role in cancer development and progression. Targeting iron and its metabolism mediators could be a novel therapeutic strategy in cancer.Deferasirox (DFX) inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…In recent years, it has been proved that ELT is also able to bind the main intracellular iron form Fe 3+ , showing iron chelating properties [ 71 , 96 , 101 , 103 , 107 , 108 ]. In particular, in 2017 Vlachodimitropoulou et al demonstrated in both human hepatoma cells (HuH7) and rat cardiomyocytes (H9C2) that ELT is a powerful iron chelator responsible for intracellular iron concentration reduction and iron mobilization when it was combined with other chelators, through a shuttling mechanism [ 108 ].…”
Section: Eltrombopag As An Anti-inflammatory Moleculementioning
confidence: 99%
“…In recent years, it has been proved that ELT is also able to bind the main intracellular iron form Fe 3+ , showing iron chelating properties [ 71 , 96 , 101 , 103 , 107 , 108 ]. In particular, in 2017 Vlachodimitropoulou et al demonstrated in both human hepatoma cells (HuH7) and rat cardiomyocytes (H9C2) that ELT is a powerful iron chelator responsible for intracellular iron concentration reduction and iron mobilization when it was combined with other chelators, through a shuttling mechanism [ 108 ].…”
Section: Eltrombopag As An Anti-inflammatory Moleculementioning
confidence: 99%
“…Notably, robust evidence supports ELT iron chelation properties that could ameliorate the fitness of HSCs and hematopoiesis, especially considering that SAA patients are frequently transfusion-dependent ( Vlachodimitropoulou et al, 2017 ; Zhao et al, 2018 ). Moreover, the ELT-mediated mobilization of intracellular iron and the decrease of serum ferritin levels observed in various clinical contexts ( Roth et al, 2012 ; Vlachodimitropoulou et al, 2017 ; Punzo et al, 2018 ; Zhao et al, 2018 ; Argenziano et al, 2021 ) could help to prevent long-term multi-organ complications and improve BM function.…”
Section: Saa: Unlock the Stemnessmentioning
confidence: 99%
“…Moreover, preliminary studies aiming to evaluate ELT efficacy and safety in the context of MDS and AML did not show increased blast proliferation or clonogenic properties, while confirming the improvement in platelets counts ( Will et al, 2009 ; Mavroudi et al, 2011 ). Furthermore, ELT showed antileukemic effects related to its iron chelation properties, the capacity to activate pro-apoptotic signaling through reactive oxygen species (ROS) modulation and induce cellular differentiation ( Roth et al, 2012 ; Kalota et al, 2015 ; Argenziano et al, 2021 ). Against this background, results from MDS and AML trials confirm ELT effectiveness in treating hypoplastic and low to intermediate-1 risk MDS, while data from higher-risk MDS and AML are conflicting and affected by the rates of clonal evolution and disease progression ( Buckstein, 2015 ; Mittelman et al, 2018 ; Frey et al, 2019 ; Vicente et al, 2020 ).…”
Section: Mds and Aml: A Dangerous Pathmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacological effect of EPAG interactions with TPO-R results in an increase of differentiation and proliferation rate of the megakaryocytoblastic cellular line and its precursors. Alongside this effect on platelet count, recent evidence also suggests an immune-modulating and iron chelating property of EPAG ( Argenziano et al, 2021 ; Di Paola et al, 2021 ).…”
Section: Introductionmentioning
confidence: 98%